Ammonium·18-crown-6 bis(trifluoromethylsulfonyl)amide. (8th September 2020) - Kawata, Kio; Kitada, Atsushi; Fukami, Kazuhiro; Murase, Kuniaki
Abstract : We report synthesis and characterization of an ammonium-based molten salt, ammonium bis(trifluoromethylsulfonyl)amide-18-crown-6 (1/1), i.e. [NH4 + ·18C6][Tf2 N – ] (Tf = SO2 CF3 ). Raman spectra shows [NH4 + ·18C6][Tf2 N – ] consists of NH4 + ion encapsulated by 18C6 and Tf2 N – anion. The melting point of [NH4 + ·18C6][Tf2 N – ] was around 100°C. At 140°C, the viscosity of [NH4 + ·18C6][Tf2 N – ] was 14.7 mPa s, the conductivity was 8.0 mS cm –1, and the density was 1.23 g cm –3 . These properties were comparable to those of common ionic liquids.